(untitled) (Italian Journal of Public Health, 2007)
Stroke is the third leading cause of mortality and the first cause of disability in Italy, with an estimated incidence of non-fatal cases of stroke of 10 cases/1000 person years among hypertensive patients, and a prevalence of ischemic stroke in the year 2001 of 5.4/1000 persons. The main responsibility for the primary prevention of stroke should be with the primary care physicians as they are best positioned to determine an atrisk population and to initiate educational, lifestyle, and cardiovascular risk reduction treatments. In primary prevention, only well-documented and potentially modifiable risk factors should be tackled. Recognition of the most relevant modifiable risk-factors leads to corresponding interventions. However, data from surveys conducted in general practice clearly demonstrate an overall under-monitoring or under-treatment for themost relevant risk factors, such as high blood pressure, smoking status, high cholesterol level, atrial fibrillation, and left ventricular hypertrophy, which led to a corresponding low treatment prevalence amongmoderate and highrisk stroke patients. In this context, the use of automatic electronic reminders has shown promising results in improving the performances of primary care physicians in the primary prevention of high-risk cardiovascular patients. This suggests there is a need for further research in general practice to evaluate the effect of such a system in improving the prognosis of individuals at high-risk of stroke.